Are shadow economy and tourism related? international evidence - Din, Badariah; Habibullah, Muzafar Shah; Abdul Hamid, Baharom; Saari, Mohd Yusof (Elsevier, 2016)
The present study attempts to investigate whether shadow economy and the tourism sector are related. In the European countries, Schneider reported that 20 to 25 per cent of the shadow economy is represented in the tourism-related industries – wholesale and retail, automotive and motorcycle sales and maintenance; transportation, storage and communications; and hotels and restaurants. For the tourism sector, the services given by operators (unregistered and/or underreporting) operate in the shadow economy will ultimately wiped off the map of high quality tourist destinations and destroyed the development of the tourism industry itself. This study examines the short-run and long-run relationships between international tourism receipts and shadow economy for 149 countries over the period 1995-2008. We use a generalized one-step error-correction model (ECM) in combination with a system Generalized Method of Moments (GMM) to explore the long-run relationship between these two variables. Our results suggest that tourism receipts and shadow economy are cointegrated. This implies that shadow economy and the tourism industry worldwide are related in the long-run. The long-run elasticities indicate a negative impact of the shadow economy on the tourism sector suggesting that increase in shadow economy activities will adversely affecting the tourism industry.